Fintech, regulatory arbitrage, and the rise of shadow banks - Buchak, Greg; Matvos, Gregor; Piskorski, Tomasz; Seru, Amit (Journal of Financial Economics, 2018)
Founded in 1920, the NBER is a private, non-profit, non-partisan organization dedicated to conducting economic research and to disseminating research findings among academics, public policy makers, and business professionals.